Effectiveness of the Value Added Tax Exemption Policy on Gross Domestic Product in Selected ASEAN Countries Towards a Conducive Business Environment Model - Atty. Prackie Jay T. Acaylar (Center for Risk Management & Sustainability and RSF Press, 2021)
Excessive exemption is detrimental to the effectiveness of the whole Value Added Tax system. This research is primarily focused on VAT exemption affecting the business industry as it influences the Gross Domestic Product of the three (3) selected ASEAN countries, namely, the Philippines, Indonesia, and Singapore. The result of the study showed a negative relationship between VAT exemption policy and GDP growth rate among the selected ASEAN economies. Although the VAT collections among the selected ASEAN countries are significantly increasing with the course of time, the results showed that as the number of VAT exemptions increases by one unit, the degree of growth of the GDP is expected to decrease at a rate of 0.900 units. Thus, a conducive business environment may be achieved by decreasing the number of VAT exemptions and, accordingly, increasing the GDP growth rate.